2006
DOI: 10.1364/ao.45.003352
|View full text |Cite
|
Sign up to set email alerts
|

Diode-pumped, continuous-wave Tm:YAIO_3 laser

Abstract: A continuous-wave, diode-pumped, room-temperature Tm:YAlO3 laser was built, characterized, and compared with a theoretical model. Spectroscopic parameters of the laser crystal, such as the pump band ((3)H4 manifold) lifetime, the upper laser level ((3)F4 manifold) lifetime, and the absorption coefficient were measured. The experimental data were used to calculate the quantum efficiency of Tm self-quenching of the (3)H4 manifold.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The absorption band of the Tm 3+ -doped crystals matches the emission wavelength of the high brightness InGaAs laser diodes, which makes direct diode pumping possible. A large number of thulium-doped crystals have been recognized as very interesting active media for diode-pumped ∼ 2 µm laser os-cillators such as Tm:YAG, Tm:YLF, Tm:KLu(WO 4 ) 2 , and Tm:KYW [3][4][5][6][7][8][9][10]. Tm:YAlO 3 (Tm:YAP) crystal is aroused widespread concern in recent years as a laser material near 2 µm [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The absorption band of the Tm 3+ -doped crystals matches the emission wavelength of the high brightness InGaAs laser diodes, which makes direct diode pumping possible. A large number of thulium-doped crystals have been recognized as very interesting active media for diode-pumped ∼ 2 µm laser os-cillators such as Tm:YAG, Tm:YLF, Tm:KLu(WO 4 ) 2 , and Tm:KYW [3][4][5][6][7][8][9][10]. Tm:YAlO 3 (Tm:YAP) crystal is aroused widespread concern in recent years as a laser material near 2 µm [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Laser emission from Tm:YAP crystal was first demonstrated with flash-lamp pumping [10] and then using Ti:sapphire laser pumping [11]. Currently, it has been demonstrated that diode pumping is the most efficient way for Tm:YAP laser pumping [12,13]. The Tm:YAP single crystal is attractive as active material for 2-µm lasers mainly due to its natural birefringence combined with good thermal and mechanical properties similar to those of the YAG crystal [8].…”
Section: Introductionmentioning
confidence: 99%
“…The wavelength around 2.0 μm is not only a strong absorption peak of water, but also widely used in medical, military, remote detection [1][2][3] and other fields, such as pumping of Ho:YAG. If Ho:YAG can be directly pumped by a Tm laser, the problem of Ho:Tm upconversion in Ho:Tm:YAG can be obviated, which will lead to more efficient Ho:YAG laser operation [4]. YALO 3 also has good thermal and mechanical properties, similar to YAG.…”
Section: Introductionmentioning
confidence: 99%